Evaluation of recombinant factor VIIa, tranexamic acid and desmopressin to reduce prasugrel-related bleeding: A randomised, placebo-controlled study in a rabbit model. Issue 3 (March 2018) - Bonhomme, Fanny; Lecompte, Thomas; Samama, Charles M.; Godier, Anne; Fontana, Pierre
Abstract : BACKGROUND: Prasugrel is a thienopyridine that inhibits platelet aggregation more rapidly and effectively than clopidogrel, with an increased bleeding risk. OBJECTIVE: The current study aimed to evaluate the efficacy of three nonspecific haemostatic drugs – recombinant activated factor VII (rFVIIa), tranexamic acid and desmopressin (DDAVP) – to limit blood loss after administration of prasugrel in a rabbit model of bleeding while also evaluating any prothrombotic effects. DESIGN: Randomised, placebo-controlled study. SETTING: Faculty of Medicine, University of Geneva, Switzerland, in 2013. ANIMALS: Anaesthetised and artificially ventilated rabbits ( n =56). INTERVENTIONS: Animals were randomly allocated to one of five groups: control (placebo–placebo), prasugrel–placebo, rFVIIa (prasugrel–rFVIIa 150 μg kg −1 ), tranexamic acid (prasugrel–tranexamic acid 20 mg kg −1 ) or DDAVP (prasugrel–DDAVP 1 μg kg −1 ). Two hours after an oral prasugrel loading dose (4 mg kg −1 ), a stenosis and an injury were inflicted on the carotid artery to induce cyclic flow reductions (CFRs) due to thrombosis. Haemostatic drugs were administered during the ensuing observation period. MAIN OUTCOME MEASURES: Standardised hepatosplenic sections were performed to evaluate the primary endpoint of blood loss, monitored for 15 min. Ear-immersion bleeding time and incidence of CFRs were secondary endpoints. RESULTS: Prasugrel decreased ADP-induced platelet aggregation (light transmission method) from 66 ± 4% (mean ± SD) to 41 ± 7% ( P < 0.001) and doubled blood loss: 10.7 g (10.1 to12.7) [median (interquartile range)] vs. 20.0 g (17.0 to 24.4), P = 0.003 in the control and prasugrel–placebo groups, respectively. rFVIIa, tranexamic acid and DDAVP reduced neither hepatosplenic blood loss [19.7 g (14.0 to 27.6), 25.2 g (22.6 to 28.7) and 22.9 g (16.8 to 28.8), respectively] nor bleeding time compared with placebo. Regarding safety, rVIIa induced three or more CFRs in 5/12 rabbits, vs. 0/12 in the prasugrel–placebo group ( P = 0.037), whereas tranexamic acid and DDAVP did not increase them. CONCLUSION: The three studied haemostatic drugs rFVIIa, tranexamic acid and DDAVP failed to reduce prasugrel-related bleeding in this model. rFVIIa-treated rabbits were more prone to arterial thrombotic events. TRIAL REGISTRATION: NA.